Guidelines for laboratory works on the topic "The study of the ground connector’s resistance to electric current flow" - Mezentseva, I. O.; Ilinska, O. I.; Yevtushenko, N. S. (My University, 2022)
Guidelines for laboratory works are intended for practical work from the course "Fundamentals of Occupational Safety and Health" of the first (bachelor's) level of training for students of higher education in the specialties of the NTU "KhPI". The goal of the work – to investigate the resistance of a ground connector to electricity current flow depending on the grounder’s parameters and design; to determine the quotient of the use of group ground connection.
Keywords: guidelines; artificial ground connectors; the utility quotient of ground connectors; electric current; voltage